RISK FACTORS FOR THE DEVELOPMENT OF VENOUS THROMBOEMBOLISM IN PATIENTS WITH UNCOMPLICATED ACUTE CALCULOUS CHOLECYSTITIS - Mariya Kavka (Acta Medica Leopoliensia)
The aim is to identify and analyze risk factors for venous thromboembolism in patients diagnosed with uncomplicated acute calculous cholecystitis.